Effect of plantation age on plant and soil C:N:P stoichiometry in Kentucky bluegrass pastures - Wei, Xiaoxing; He, Keyan; Wang, Qian; Liu, Wenhui; Pang, Xiaopan; Guo, Zhenggang (Frontiers in Sustainable Food Systems, 2024)
Plant and soil C:N:P stoichiometry reflects the element content and energy flow, which are important for biogeochemical cycling in ecosystems. Although plantation age has been verified to affect leaf C:N:P in alfalfa plants, the effect of plantation age on plant and soil C:N:P in grass is not well documented. Kentucky bluegrass (Poa pratensis) was considered as a focal grass to test how plantation age affect plant and soil C:N:P stoichiometry in a perennial rhizomatous grass pasture. This study showed that leaf C:N, C:P and N:P showed a rapid increase trend from 2-year age to 6-year age, whereas leaf C:N showed a slight decrease trend, and leaf C:P and N:P maintained stable from 6-year age to 9-year age. Stem C:N and N:P were not different among plantation ages, while the stem C:P increased from 2-year age to 4-year age, and then maintained stable from 4-year age to 9-year age. Root N:P showed an increasing trend from 2-year age to 6-year age, and a relative stability from 6-year age to 9-year age, whereas root C:N and C:P showed the decreasing trends during 2-year age to 9-year age. Although soil C:P was not different among nine plantation ages, whereas soil C:N and N:P maintained relatively stable from 2-year age to 6-year age, and soil C:N showed a decrease trend and N:P showed an increasing trend after 6-years age. The results from ecological stoichiometric homeostasis analysis further showed that N in leaf, stem and root, and P in stem had strict homeostasis, whereas the P in leaf and root showed plastic and weakly homeostatic status, respectively. These results present a pattern concerning the plantation age in relation to plant and soil C:N:P stoichiometry in a perennial grass and provide useful information for N and P management in kentucky bluegrass pastures.